2020
DOI: 10.1186/s12906-020-02890-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of limonin in anticancer effects of Evodia rutaecarpa on ovarian cancer cells

Abstract: Background: Ovarian cancer therapy generally involves systemic chemotherapy with anticancer drugs; however, chemotherapy with a platinum-based drug has often been shown to cause adverse reactions and drug resistance in ovarian cancer patients. Evodia rutaecarpa (ER) reportedly shows anticancer activity against various types of cancer cells. However, the effects of ER have not yet been fully uncovered in ovarian cancer. Methods: In the present study, we investigated the anticancer effects of an ER extract and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…It is a secondary metabolite that is widely found in citrus fruits [ 7 ]. Numerous studies have shown that limonin exhibits a wide spectrum of biological and pharmacological activities, including anti-cancer [ 8 , 9 , 10 ], anti-inflammatory [ 10 , 11 ], anti-oxidative [ 12 ], anti-viral [ 13 ], and liver-protective properties [ 14 , 15 ]. Hesperidin, or vitamin P, is a flavanone glycoside found in all types of citrus fruits.…”
Section: Introductionmentioning
confidence: 99%
“…It is a secondary metabolite that is widely found in citrus fruits [ 7 ]. Numerous studies have shown that limonin exhibits a wide spectrum of biological and pharmacological activities, including anti-cancer [ 8 , 9 , 10 ], anti-inflammatory [ 10 , 11 ], anti-oxidative [ 12 ], anti-viral [ 13 ], and liver-protective properties [ 14 , 15 ]. Hesperidin, or vitamin P, is a flavanone glycoside found in all types of citrus fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that several active Evodia compounds exert cytotoxic effects on human cancer cell lines. Speci cally, evodiamine has an inhibitory effect on human lung cancer A549 cells [32], and limonin in Evodia induces apoptosis in ovarian cancer cells by activating the p53 signaling pathway [33]. Additionally, evodiamine plays an important role in activating JNK and PERK in human ovarian cancer cells to induce apoptosis [34] and inhibits the proliferation of hepatocarcinoma cells through a WWOX-dependent pathway to induce anticancer activity [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bae et al. (2020) found that limonin can induce cell apoptosis by activating p53 signal pathway, reducing the viability of SKOV‐3, A2780, and RMUG‐S ovarian cancer cells, and reversing the drug resistance of CISRSKOV‐3 cells by activating apoptosis. Gong et al (2019) found that limonin can effectively inhibit lung cancer induced by benzopyrene (BP) in mice, and in vitro experiments showed that limonin can promote the production of reactive oxygen species (ROS) and induce apoptosis of A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%